Valley-exchange coupling probed by angle-resolved photoluminescence. Issue 1 (19th November 2021) - Thompson, Joshua J. P.; Brem, Samuel; Fang, Hanlin; Antón-Solanas, Carlos; Han, Bo; Shan, Hangyong; Dash, Saroj P.; Wieczorek, Witlef; Schneider, Christian; Malic, Ermin
Abstract : We propose that angle-resolved photoluminescence can be employed as an unambiguous detection scheme to determine the role of the valley exchange-interaction in the excitonic properties of TMD monolayers. Abstract : The optical properties of monolayer transition metal dichalcogenides are dominated by tightly-bound excitons. They form at distinct valleys in reciprocal space, and can interact via the valley-exchange coupling, modifying their dispersion considerably. Here, we predict that angle-resolved photoluminescence can be used to probe the changes of the excitonic dispersion. The exchange-coupling leads to a unique angle dependence of the emission intensity for both circularly and linearly-polarised light. We show that these emission characteristics can be strongly tuned by an external magnetic field due to the valley-specific Zeeman-shift. We propose that angle-dependent photoluminescence measurements involving both circular and linear optical polarisation as well as magnetic fields should act as strong verification of the role of valley-exchange coupling on excitonic dispersion and its signatures in optical spectra.